Capital Flows and the Twin Crises : The Role of Liquidity - Goldfajn, Ilan (IMF Working Papers; Working Paper ;, 1997)
This paper develops a model that focuses on the interaction of liquidity creation by financial intermediaries with capital flows and exchange rate collapses. The intermediaries' role of transforming maturities is shown to result in larger movements of capital and a higher probability of crisis. These movements resemble the observed cycle in capital flows: large inflows, crisis and abrupt outflows. The model highlights how adverse productivity and international interest rate shocks may trigger a sudden outflow of capital and an exchange collapse. The initial shock is magnified by the behavior of individual foreign investors linked through their deposits in the intermediaries. The expectation of an eventual exchange rate crisis links investors' behavior even further.